Pengaruh penerapan bahan ajar interaktif bermuatan karakter menggunakan model pembelajaran discovery learning pada materi fluida terhadap pencapaian kompetensi siswa kelas XI SMAN 7 Solok Selatan - Yunita Ela Saputri; Yenni Darvina; Amali Putra; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2019)
Interactive teaching materials play an important role to achieve success in the learning process. The reality is at school, learning physics has not used interactive teaching materials only printed teaching materials are available in the library. The implementation of learning still applies the lecture method and does not use the model of learning. The application of character values has not been integrated in teaching materials. Overcoming the problem is given a solution that is applying Character Loaded Interactive Teaching Materials. The purpose of this study was to examine the effect of Interactive Character-Based Teaching Materials using the Discovery Learning Model on the Achievement of Students of Class XI SMAN 7 Solok Selatan. This type of research is a quasi-experimental research design using the Posttest Only Nonequivalent Control Group Design. The study population was all students of class XI MIA SMAN 7 Solok Selatan. The technique of determining the sample is done by combining purposive sampling and cluster random sampling techniques. The research sample is class XI MIA 2 for the experimental class and class XI MIA I as the control class. Instruments for obtaining data in the form of an attitude observation sheet and posttest sheet. Processing data using normality test, homogeneity test, hypothesis test, simple linear regression and correlation test at the real level of 0.05. The results showed that the average value of experimental class knowledge competence was higher than the average value of control class knowledge competence of 81.08 and 72.24. The result of product moment correlation analysis on knowledge competence is 24.88% and attitude competency is 25.31%. Based on the results of the study it can be concluded that at the real level of 0.05 there is a significant influence of the application of Character-Based Interactive Teaching Materials using the Discovery Learning Model for the Achievement of Students in Class XI of SMAN 7 Solok Selatan.